Strengthening Religious Character through Habituation Program at SMA Negeri 4 Gorontalo - Bialangi, Saiful S; Masaong, Abdul Kadim; Mas, Sitti Roskina (International Research-Based Education Journal, 2023)
This study aims to: (a) know the implementation of the habituation process, (b) know that the habituation program can improve the religious character of students at SMA Negeri 4 Gorontalo. This research uses a quantitative approach with a school Action research design. The data collection technique uses questionnaires in the form of questionnaires which are used to capture data on (a) student character, (b) stages of implementation of habituation programs to improve the quality of student character, non-participant observations, namely researchers are not directly involved and only as independent observers, researchers record, analyze, and make conclusions about the application of character education in improving student character through the implementation of habituation programs in high school Negeri 4 Gorontalo, and study documents are documents in the form of lesson plan examples, school profiles, and photos of research activities related to the application of character education. The results showed that; (1) The implementation of the habituation process at SMA Negeri 4 Gorontalo which is carried out through 6 activities, including (a) the implementation of Dhuha prayers, (b) congregational zuhr prayers, (c) alms infaq movement (GARISA), (d) reading a holy book, (e) “jumpa berlian”, and (f) “budaya lisa”. Cycle I is in a good category and cycle II is in a very good category. (2) The habituation program can improve the religious character of students at SMA Negeri 4 Gorontalo, this is shown by the average results of achievements in cycle II which shows that the religious character of students has increased significantly with excellent categories. This shows that there is an increase in student awareness to carry out religious activities to be able to improve the quality of student character optimally.